2007
DOI: 10.1002/pssc.200673825
|View full text |Cite
|
Sign up to set email alerts
|

Optically‐detected magnetic resonance of molecular color centers CO3 and NO3 in gamma‐irradiated beryl

Abstract: In this paper we identify, with optically-detected magnetic resonance via the magnetic circular dichroism of the absorption, the NO 3 and CO 3 -molecular radicals trapped in the structural channels of gammairradiated beryl. We confirm that, along with the CO 3 -, the NO 3 is also responsible for the blue color by introducing several absorption peaks between 14500 cm -1 and 18000 cm -1 (720 nm down to 540 nm). Their individual contributions to the overall many-peak optical spectra have been established and most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Similar absorption bands and ESR were observed previously in other irradiated materials containing carbonate anion groups (CO 3 ) 2-, including cancrinite (Shendrik et al, 2021;, calcite (Chantry et al, 1962;Serway and Marshall, 1967), irradiated Maxix beryl where (CO 3 ) 2anion groups are located in channels (Pinheiro et al, 2007). The observed ESR and absorption bands are associated with the formation of (CO 3 ) •hole radicals.…”
Section: Discussionsupporting
confidence: 85%
“…Similar absorption bands and ESR were observed previously in other irradiated materials containing carbonate anion groups (CO 3 ) 2-, including cancrinite (Shendrik et al, 2021;, calcite (Chantry et al, 1962;Serway and Marshall, 1967), irradiated Maxix beryl where (CO 3 ) 2anion groups are located in channels (Pinheiro et al, 2007). The observed ESR and absorption bands are associated with the formation of (CO 3 ) •hole radicals.…”
Section: Discussionsupporting
confidence: 85%
“…All these peaks are thermally unstable and are probably due to extrinsic colour centres related to the presence of CO 3 2-or NO 3- [8][9][10]. In these centres the electronic transitions interact with a localized vibration that may be difficult to detected since, in the 1000 cm -1 region, the absorption due to the host lattice is quite strong.…”
Section: The Absorption Of Intrinsic and Extrinsic Colour Centresmentioning
confidence: 99%
“…The precise identity of the intriguing Maxixe and "Maxixe type" centres [7] is, probably, not yet conclusively established, although EPR measurements [8][9][10] on these paramagnetic centres have concluded that are due to CO 3 and NO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, beryl has been well characterised by spectroscopy techniques [8][9][10][11], ESR [12,13], Mössbauer spectroscopy [14,15] but no previous work on beryl CL has been performed. Only Ref.…”
Section: Introductionmentioning
confidence: 99%